A study of impairment and disability among elderly and its effect on health-related quality of life - Kamat, Apurva; Shah, Hemangini K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Ageing is generally defined as a process of deterioration in the functional capacity of an individual that results from structural changes, with increasing age. Although old age is not a disease in itself; the elderly are vulnerable to chronic diseases like cardiovascular illnesses, cancers, diabetes etc. leading to impairment and disabilities affecting the health related quality of life of the elderly (HRQOL), which has become an increasingly important outcome in public health research. The main aim is to estimate the common impairments and disabilities among elderly and its effect on their health-related quality of life. Methods: In the community based cross-sectional study, among 171 elderly (more than or equal to sixty years of age) selected from the field practice area of Urban Health Centre of a tertiary care center, Goa, through simple random sampling technique, the data was collected using a pre designed structured questionnaire eliciting previously diagnosed health related conditions, SF-36 HRQOL questionnaire and a detailed general examination. Data was analysed using Epi Info version 7.00 statistical package and various tests of significance were used. Results: Of total of 171 elderly, 56.14% were impaired. The HRQOL and domain scores decreased with increasing age with lower mean scores in females than males (p=0.039). Age, marital status, three generation families, absence of co-morbidities, impairment and disability, education, occupation were significant favorable influences on the HRQOL in (total and domain scores), role of physical domain being the most commonly affected. Conclusions: The increasing population of elderly more so the female elderly population, the emergence of double burden of communicable and non-communicable diseases, presence of impairments and disabilities severely affects their HRQOL.